En bloc resection for nonmuscle-invasive bladder cancer: selecting a proper laser - Enikeev, Dmitry; Babjuk, Marek; Shpikina, Anastasia; Shariat, Shahrokh; Glybochko, Petr (Current opinion in urology, 2022)
PURPOSE OF REVIEW: To discuss the most recent surgical lasers that have been made available to us and to evaluate their potential in performing en bloc resection of nonmuscle invasive bladder cancer. RECENT FINDINGS: Laser en bloc resection of bladder tumors (ERBT) can be performed with a number of laser systems including Ho:YAG, GreenLight, diode, Tm:YAG and thulium fiber lasers (TFL). The data that is currently available suggests that the water-targeting devices (utilizing water as a primary chromophore - Ho:YAG, Tm:YAG, TFL) may have a number of advantages over hemoglobin-targeting systems (potassium titanyl phosphate:YAG, lithium triborate:YAG). One recent addition to the surgical armamentarium Moses effect enhanced Ho:YAG and the TFL (being able to work both in quasi-continuous and SuperPulsed modes) necessitates careful discussion and comparison with the other available devices. SUMMARY: The majority of available lasers have proven to be safe to use and compared to electrocautery allow for lower rates of obturator nerve reflex and result in fewer bleeding complications. The minimal penetration depth and decreased peak power of Tm:YAG and TFLs render them the devices of choice when it comes to ERBT. Unfortunately, more studies on ERBT with TFL are needed in order for us to make a sound assessment of the respective pros and cons.
Keywords: Lithotripsy, Laser; thulium; Lasers, Solid-State; mužské pohlaví; Thulium; Urinary Bladder Neoplasms; ženské pohlaví; laserová litotripse; lasery pevnolátkové; Humans; Water; Female; nádory močového měchýře; lidé; Male; voda